Analisis Faktor-Faktor yang Mempengaruhi Nilai Tukar Rupiah Periode 1999Q1-2019Q2 - Erric Wijaya (Universitas Samudra, 2020)
The exchange rate plays an important role in influencing the level of Indonesia's international trade towards trading partner countries. This study discusses the factors that influence the exchange rate of the rupiah against dollar both in the short and long term. The variables that are suspected to influence changes in exchange rates are the inflation rate, the interest rate (SBI), world oil prices, the value of exports, and the value of imports. This research was conducted during 1999 quarter 1 to 2019 quarter 2. The results showed that there was a long-term and short-term relationship between inflation rates, interest rates, world oil prices, exports and imports to the exchange rate. In the short term, the interest rate and world oil prices have a significant effect on the exchange rate. In the long run, the inflation rate, world oil prices and imports have a significant effect on the exchange rate.